Pengaruh Intervensi Susu Kedelai yang Difortifikasi Bubuk Daun Kelor terhadap Peningkatan Status Gizi Balita: Effect of Intervention of Soy Milk Fortified with Moringa Leaf Powder on Improving Nutritional Status - Nur Chabibah; Milatun Khanifah; Pujiati Setyaningsih (Amerta Nutrition, 2023)
Background: Wasting and stunting status in children impacts growth and development. One of these efforts is providing supplementary food and local food-based recovery with regional specialties. The local plants can be fortified with food additives. Objective: To determine the effectiveness of fortification of Moringa leaf powder in soy milk to improve the nutritional status of children under five. Methods: The research design used a quasi-experimental design with a pre-test and post-test control design group approach. This study used total sampling with 15 children under five in the intervention and control groups. The intervention provided was education with toddler nutrition booklets and the provision of 100 CCs of soy milk that had been fortified with 0.32 mg. It was given for two consecutive months with a frequency of three to four times weekly. The control group was given education and nutrition booklets for toddlers. Results: The results of this study showed that there was a significant difference between the mean difference in body weight (BB) in the intervention group and the control group (p-value: 0.001 CI: -0.911-(-0.245)). However, the difference in mean height (TB) in the intervention group and the control group showed no significant difference (p-value; 0.157; CI 2.244 – 0.38)). There was a significant increase in nutritional status in the intervention group (p-value: 0,009 CI: (-1.159 – (-0.174) Conclusion: Fortification of Moringa powder in soy milk can increase the weight of toddlers with poor nutritional status.